Venture capital and firm performance over the long-run: Evidence from high-tech IPOs in the United States - James R. Brown (The Journal of Entrepreneurial Finance and Business Ventures, 2005)
Despite widespread interest in the key role that venture capital plays in financing young, high-tech firms, little is known about the relative performance of venture-backed firms over the long-run. Using data from the U.S. high-tech sector, this paper examines the performance and financing of venture- and non-venture-backed firms during the decade following their IPO. Venture-backed firms survive longer, grow faster, are more R&D intensive, have generally superior operating performance, raise more external equity, and have a greater cumulative impact on the U.S. high-tech sector. These findings suggest that the true legacy of venture capital finance extends well beyond the IPO.
Keywords: 650